Relationship between epicardial adipose tissue volume and atrial fibrillation in patients with rheumatoid arthritis - Yao, Hao; Chen, Jian; Li, Xueling; Zhang, Xin (Frontiers in Cardiovascular Medicine, 2025)
IntroductionEpicardial adipose tissue (EAT) is involved in cardiac inflammatory responses and has been associated with both atrial fibrillation (AF) and rheumatoid arthritis (RA). However, the condition of EAT in patients with both RA and AF is still unclear. In addition, the risks of stroke and bleeding in patients with both RA and AF are unknown.MethodsA retrospective analysis was conducted in patients with RA aged ≥18 years from August 2021 to May 2023, and compared with age- and gender-matched patients without RA. The volume of EAT was measured using chest computed tomography and the EAT/body mass index (BMI) ratio was used to correct for the possible impact of BMI differences. The stroke and bleeding risks of the patients were assessed using the CHA2DS2-VASc or HAS-BLED scores.ResultsA total of 145 patients with RA and 282 patients without RA were included. The volume of EAT or EAT/BMI ratio was similar between the patients with RA and no AF and those without both RA and AF. Compared to the patients without AF, those with AF had a larger EAT volume or EAT/BMI ratio, regardless of whether they had RA or not. EAT/BMI ratio was significantly associated with left atrial (LA) diameter among the patients with RA (RR = 2.23, P < 0.001) but not among the patients without RA (P < 0.954). The RA groups had larger LA-EAT volume (31.53 ± 11.02 mm3 vs. 22.56 ± 9.58 mm3, p < 0.001) and LA-EAT/Total EAT ratio (23.02% ± 3.62% vs. 18.74 ± 3.38 mm3, p < 0.001) than that in non-RA groups. In addition, the proportion of patients with high stroke risk scores was higher among the patients with both RA and AF compared to those without RA but with AF (90.90% vs. 72.00% in men; 84.78% vs. 71.11% in women), while the proportion of patients with high bleeding risk scores was lower (22.06% vs. 27.85%).ConclusionLA diameter correlates with the EAT/BMI ratio in patients with RA who exhibit larger LA-EAT volume and LA-EAT/total EAT ratios compared to individuals without RA.